Ethnic issues in the works of John Steinbeck - Vičič, Polona (Acta neophilologica, 2012)
John Steinbeck is an author whose literary oeuvre has evoked a rich palette ofreactions, from open admiration to total rejection. This divided reaction tohis works is probably at least to some extent due to the fact that his worksaddress several contentious issues, one of them being ethnic issues, which will be discussed in this paper.
Keywords: American literature; ameriška književnost; ethnic issues; ethnicity; etnična vprašanja; etničnost; Literarne študije; Steinbeck, John, 1902-1968